[PP.28.14] BENEFIT OF FORTY-EIGHT-HOUR AMBULATORY BLOOD PRESSURE MONITORING IN HEMODIALYSIS POPULATION. (September 2016) - Mnif, K.; Jarraya, F.; Chaker, H.; Mahfoudh, H.; Feki, S.; Charfeddine, S.; Abid, L.; Kammoun, S.; Kammoun, K.; Hachicha, J.
Abstract : Objective: Data derived from ambulatory BP (blood pressure) monitoring (ABPM) allow better characterization of BP during everyday activities and sleep, and, most importantly, better correlate with target organ damage, cardiovascular disease (CVD) risk, and long-term patient prognosis than clinic BP. The aim of our work is to define the role of ABPM in hemodialysis (HD) patients and assess the correlation of its results with the echocardiographic data. Design and method: The study has a cross-sectional design. We enrolled 17 patients. We performed ABPM for 48 hours (day of dialysis (D1), day following dialysis (D2)) in all patients. ABPM was recorded every 20 min during the day and every 30 min during the night. Dialysis unit BP recordings measured before and after dialysis were collected prospectively at the time of the patient visit. Two-dimensional- guided M-mode echocardiograms were performed before and after HD. Results: According to the collected BP before HD, 4 (23.5%) patients had HTN, against 10 (58.8%) according to the measures taken after HD. According to ABPM, we defined 4 categories of BP: 5 (29.4%) patients were normotensive, 4 (23.5%) with sustained HTN, 4 (23.5%) with masked HTN and 4 (23.5%) with white- coat HTN. Systolic BP of 48 H correlated significantly with pre and post dialysis BP (p < 0.05). Pulse pressure (PP) of 48 H correlated significantly with pre and post dialysis PP (p < 0.01). The study of the variation of nocturnal BP objectified a dipper profile in 3 cases (17.6%), non-dipper in 12 cases (70.6%), inverted-dipper in 2 cases (11.8%). Three patients (17.6%) had echocardiographic left ventricular hypertrophy. We found a significant decrease in the mass of the left ventricle after HD from 318.41 g / m2 ± 71.21 to 261.95 g / m2 ± 86.56 (p = 0.002). Conclusions: Our study confirms the high prevalence of BP abnormalities at the ABPM in HD population. Not only ABPM helps in the diagnosis and categorization of HTN, but can also provide prognostic. We suggest that ABPM should become the norm for the diagnosis of HTN and prognostic evaluation in chronic HD population.